Diversity of orchids (Orchidaceae) and host trees at Padang, West Sumatra, Indonesia: A preliminary step towards germplasm conservation - Setiawan, Ryan Budi; Handayani, Mellyyana; Rahimmi Nanda, Alifma; Sukma, Dian; Rahmi, Alfazlul; Syahputra, Agil (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Orchid exploration brings numerous benefits, including the conservation of rare species, ecological insights, medicinal and horticultural applications, economic opportunities, cultural appreciation, and scientific advancement. These benefits underscore the importance of continued exploration and conservation efforts to safeguard orchid diversity. This study aimed to explore the diversity of orchids at Universitas Andalas, Padang, West Sumatra. The research involved a comprehensive survey of orchid species in various habitats, documenting their distribution and abundance. We used a systematic sampling method to collect plant specimens and record relevant ecological data. The research indicated a remarkable diversity of orchid species at Universitas Andalas. We found 21 species of orchids, including 19 epiphytes and two terrestrial species. Filicium desipiens was the most dominant host, with 13 species of orchids found on 15 trees. Dendrobium crumenatum was the most common orchid found on 13 host trees. The results highlighted the importance of preserving these unique orchid populations. This research contributes to the understanding of orchid diversity at Universitas Andalas. The findings can inform policymakers, conservationists, and local communities in developing effective strategies for the preservation and sustainable use of orchid resources. Future studies should focus on further exploration, taxonomic studies, and conservation initiatives to ensure long-term survival. Keywords: conservation; diversity; epiphytes; exploration; terrestrial